1988
DOI: 10.1159/000181067
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone-Secreting Adrenocortical Tumor in a Pubertal Girl

Abstract: A girl aged 12 years and 10 months presented with deepening of the voice first noted 7 months earlier. Pubertal development was almost completed. The girl had regular monthly menses and no signs of hirsutism, clitoris enlargement or Cushing’s disease. Serum testosterone was about threefold above normal, whereas dehydroepiandrosterone was in the upper normal range. The 17-ketosteroids as well as the gas-chromatographically analyzed 5α and 5β derivatives of testosterone from urine were slightly increased. Other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Al though nonsecreting tumors have been reported, the ma jority of children manifest clinical symptoms of hormone excess such as hypercortisolemia, virilization, feminiza tion, hyperaldosteronism or combinations of these fea tures [1][2][3][4][5][6][7][8]. Both types of adrenocortical tumors (carcino mas and adenomas) produce a wide variety of steroid hor mones.…”
Section: Introductionmentioning
confidence: 99%
“…Al though nonsecreting tumors have been reported, the ma jority of children manifest clinical symptoms of hormone excess such as hypercortisolemia, virilization, feminiza tion, hyperaldosteronism or combinations of these fea tures [1][2][3][4][5][6][7][8]. Both types of adrenocortical tumors (carcino mas and adenomas) produce a wide variety of steroid hor mones.…”
Section: Introductionmentioning
confidence: 99%
“…The malignant adrenal tumor size was significantly larger than that of benign tumors, consistent with various studies on adrenal tumors. Testosterone is the most sensitive marker in the hormone evaluation of PASAT, as it is elevated in almost all PASAT patients and is the only increased androgen in certain patients ( 41 , 62 , 63 ). Some studies ( 64 , 65 ) have demonstrated that increased DS (produced uniquely by the adrenal zona reticularis) and DHEA (produced mainly by the adrenal zona reticularis) are indicators of adrenal etiology, especially DS.…”
Section: Discussionmentioning
confidence: 99%
“…In a minority of patients elevated excretion of 16c~-hydroxy DHA [6] and ll~3-hydroxy DHA [27] has been found. Testosterone producing adrenal tumours occur only rarely [20].…”
Section: Introductionmentioning
confidence: 99%